Analysis of the English Language Needs of Students at the Russian Technological University - Olga G Rossikhina; Polina V Ermakova; Olga A Aleshchenko (Peoples' Friendship University of Russia (RUDN University), 2019)
The article looks into the English language needs of engineering students and young graduates at one of the leading technological universities in Russia - NUST MISiS. The authors used a mixed methodology approach to explore how often and in what real-life situations current and former students use the English language. 107 paper questionnaires were completed by master's degree students in class and the answers were counted; 123 responses were received online from 2015 and 2016 graduates and processed statistically; 17 structured interviews with college administrators and subject professors were recorded and then coded for the main categories. The results demonstrate that despite dramatic changes at NUST MISiS under The Competitiveness Enhancement Program 5-100, good English competence is not a priority, with the majority of young graduates being 'unsure' about its benefits for their career and some administrators calling it 'the least required competence'. However, the English language needs vary across subject departments. Thus, students majoring in new materials and programming use English on a regular basis, while economists and metallurgists might not really need it in both studies and future job. Overall, the most required skill is reading, and the least used ones are oral communication and academic writing in English. The authors discuss how orientation on potential rather than actual needs can affect the ESP/EAP course design in the context of engineering education in Russia.